Evaluation of the surface damage of dental implants caused by different surgical protocols: an in vitro study. Issue 7 (July 2019) - Streckbein, P.; Wilbrand, J.-F.; Kähling, C.; Pons-Kühnemann, J.; Rehmann, P.; Wöstmann, B.; Howaldt, H.-P.; Möhlhenrich, S.C.
Abstract: The implant surface must withstand high insertion torque during implant insertion. The aim of this study was to investigate the damage to implant surfaces caused by two different insertion protocols in vitro. Fifteen titanium implants per group were inserted in standardized polyurethane foam models, group 1 according to a non-threaded surgical protocol and group 2 according to a threaded surgical protocol. Before and after insertion, the surfaces were visualized by scanning electron microscopy (SEM) and non-contact laser profilometry. Different surface area parameters were evaluated and maximum torque during insertion was determined. SEM detected topographical changes such as deposition of the test block and smoothening of the surface in the region of the thread crests in both groups. The laser profilometry analysis revealed significant changes in the surface topography of the implants in both groups, but no differences between the groups. Insertion torque was significantly decreased in the threaded group. Both types of surgical intervention resulted in surface damage. Less damage was detected to the thread crests with the use of a thread cutter, and most of the surface was not visibly affected by the surgical protocol at the microscopic level. The surgical protocol seems to have a minor influence on preservation of the implant surface.